2015
DOI: 10.1088/0953-8984/27/48/485304
|View full text |Cite
|
Sign up to set email alerts
|

Structure of amorphous Ag/Ge/S alloys: experimentally constrained density functional study

Abstract: Density functional/molecular dynamics simulations have been performed to determine structural and other properties of amorphous Ag/Ge/S and Ge/S alloys. In the former, the calculations have been combined with experimental data (x-ray and neutron diffraction, extended x-ray absorption fine structure). Ag/Ge/As alloys have high ionic conductivity and are among the most promising candidates for future memristor technology. We find excellent agreement between the experimental results and large-scale (500 atoms) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…2) in the present work may be related to the metallic component observed in the samples of Souchier et al before switching. Correspondingly, the Type-II regions in the present work may be related to the component of nonmetallic bonding detected by Souchier et al [39], and could correspond to the a-Ag-Ge-S matrix containing more of units such as Ge-AgS 3 and Ge-GeS 3 [40]. By analogy with the work of Souchier et al, a possible origin of the Type-I and Type-II regions is non-uniformity in the supply of Ag.…”
Section: Resultssupporting
confidence: 68%
“…2) in the present work may be related to the metallic component observed in the samples of Souchier et al before switching. Correspondingly, the Type-II regions in the present work may be related to the component of nonmetallic bonding detected by Souchier et al [39], and could correspond to the a-Ag-Ge-S matrix containing more of units such as Ge-AgS 3 and Ge-GeS 3 [40]. By analogy with the work of Souchier et al, a possible origin of the Type-I and Type-II regions is non-uniformity in the supply of Ag.…”
Section: Resultssupporting
confidence: 68%
“…The use of pyMolDyn is described in detail in the online documentation (see links above). To illustrate its usage, we take the attached input file AgGeS‐BOX.xyz, which shows a result of a 500‐atom simulation of an amorphous alloy of Ag, Ge, and S (Ag 100 Ge 168 S 232 ) in a cubic box of size 21.799 Å . The first three lines of the input are then:
500CUB 21.799AG −7.738 …
…”
Section: Applicationmentioning
confidence: 99%
“…The result is also consistent with the X‐ray diffraction profile of Ge 3–2 x Ag 2 x S 3 ( x = 0.6–1.0) glasses, [ 23 ] the distinct scattering function of (Ag 2 S) x (GeS 2 ) 1– x ( x = 0.3, 0.4, 0.5) glasses obtained from neutron diffraction, [ 24 ] and the X‐ray and neutron structure factors of Ag 20 (Ge 0.42 S 0.58 ) 80 glasses. [ 25 ] In every case, a large peak is observed around Q = 2.0 Å −1 . These results indicate that a new network structure is constructed involving Ag atoms by silver photodiffusion.…”
Section: Resultsmentioning
confidence: 97%
“…[ 28–30 ] Actually, the structural study of Ag x (Ge 0.42 S 0.58 ) 100– x glasses demonstrated that the cavity volume of x = 0 is much greater than that of x = 20. [ 25 ] The voids in the Ge–S network can be filled with Ag ions in the process of silver photodiffusion.…”
Section: Resultsmentioning
confidence: 99%